Constitutive and inducible nitric oxide synthase gene expression, regulation, and activity in human lung epithelial cells. - Asano, K (1994)
Histochemical activity and immunoreactivity of nitric oxide synthase (NOS, EC 1.14.13.39) have been recently demonstrated in human lung epithelium. However, the molecular nature of NOS and the regulation and function of the enzyme(s) in the airway is not known. A549 cells (human alveolar type II epithelium-like), BEAS 2B cells (transformed human bronchial epithelial cells), and primary cultures of human bronchial epithelial cells all exhibited constitutive NOS activity that was calcium dependent and inhibitable by the NOS inhibitor NG-monomethyl-L-arginine. Nitric oxide production by epithelial cells was enhanced by culture in the presence of interferon gamma, interleukin 1 beta, tumor necrosis factor alpha, and lipopolysaccharide; the NOS activity expressed under these conditions showed less dependence on calcium, reminiscent of other inducible forms of NOS. Two distinct NOS mRNA species, homologous to previously identified constitutive brain (type I) and inducible hepatic (type II) NOS, were demonstrated by reverse transcription-polymerase chain reaction in all cell lines. Northern analysis confirmed the expression of inducible NOS mRNA. Cell culture with epidermal growth factor, a principal regulator of epithelial cell function, decreased inducible NOS activity by posttranscriptional action but did not affect constitutive NOS activity. The coexistence of constitutive and inducible NOS in human alveolar and bronchial epithelial cells is consistent with a complex mechanism evolved by epithelial cells to protect the host from microbial assault at the air/surface interface while shielding the host from the induction of airway hyperreactivity.